A tool for detecting transient faults in execution of parallel scientific applications on multicore clusters - Montezanti, Diego Miguel (2014)
Transient faults are becoming a critical concern among current trends of design of generalpurpose multiprocessors. Because of their capability to corrupt programs outputs, their impact gains importance when considering long duration, parallel scientific applications, due to the high cost of re-launching execution from the beginning in case of incorrect results. This paper introduces SMCV tool which improves reliability for high-performance systems. SMCV replicates application processes and validates the contents of the messages to be sent, preventing the propagation of errors to other processes and restricting detection latency and notification. To assess its utility, the overhead of SMCV tool is evaluated with three computationallyintensive, representative parallel scientific applications. The obtained results demonstrate the efficiency of SMCV tool to detect transient faults occurrences.